2018
DOI: 10.15561/20755279.2019.0203
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of foreign female students to physical activity based on the dexterity development

Abstract: Purpose : to analyze the influence of physical qualities of foreign female students on their adaptation to physical activity. It is suggested to apply an individually-differentiated training program for this purpose. Material and methods : the comparative analysis of foreign female students from Turkmenistan, Tajikistan and Kazakhstan (n = 60) - an experimental group and females from Russian regions (n = 119) - a control group. It was applied the standards of the All-Russian sports complex "Ready for Labour an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…• decline in motor activity of the population related to universal automation and modernization of life (Osipov, Kudryavtsev, Iermakov, Yanova, Lepilina, Plotnikova, & Dorzhieva, 2017); • lack of motivation to do sports or work out (Anikieiev, 2015;Jaakkola, Yli-Piipari, Barkoukis, & Liukkonen, 2017;Sulz, Temple & Gibbons, 2016); • lack of a differentiated approach while selecting the load level at physical education classes (Nagovitsyn, Osipov, Manurov, Zhuikov, & Vershinina, 2019); • reduction of mandatory hours on physical education in nonspecialized universities and transfer of these classes to an optional or elective form (Kashuba et al, 2019;Gryban, 2014); • deterioration of ecological environment (Lebedinskiy, Koipysheva, Rybina, Kudryavtsev, Iermakov, Osipov, & Sidorov, 2017;Paliienko, 2017;Trotska, Homlia, & Kovalenko, 2018). The researchers offer a range of measures to increase the youth's fitness levels.…”
mentioning
confidence: 99%
“…• decline in motor activity of the population related to universal automation and modernization of life (Osipov, Kudryavtsev, Iermakov, Yanova, Lepilina, Plotnikova, & Dorzhieva, 2017); • lack of motivation to do sports or work out (Anikieiev, 2015;Jaakkola, Yli-Piipari, Barkoukis, & Liukkonen, 2017;Sulz, Temple & Gibbons, 2016); • lack of a differentiated approach while selecting the load level at physical education classes (Nagovitsyn, Osipov, Manurov, Zhuikov, & Vershinina, 2019); • reduction of mandatory hours on physical education in nonspecialized universities and transfer of these classes to an optional or elective form (Kashuba et al, 2019;Gryban, 2014); • deterioration of ecological environment (Lebedinskiy, Koipysheva, Rybina, Kudryavtsev, Iermakov, Osipov, & Sidorov, 2017;Paliienko, 2017;Trotska, Homlia, & Kovalenko, 2018). The researchers offer a range of measures to increase the youth's fitness levels.…”
mentioning
confidence: 99%
“…The authors of the article coincide with the opinion of a number of Russian and foreign experts about the individualization and differentiation of education based on various social and national-regional characteristics in physical education classes at a university in the development of a future specialist [1,12]. When physical training and sports training is individualized, especially for those who are not at a high level and have a first or second year of study in a new educational environment, which has been confirmed experimentally [14], significant improvements are found in the motivation to maintain a physical culture during the rest of their lives [20]. As well as physical and mental performance and physiological indicators, despite the subtle differences in the intensity of exercise and the total duration of the workout [17].…”
Section: Discussionmentioning
confidence: 53%
“…Studies show that already after the first course, students engaged in active motor activity are significantly ahead of their peers who participate in the regular program in terms of their agility characteristics in the implementation of various motor actions [7,21]. Only the implementation of a system of educational and extracurricular physical culture and sports activities can enhance the effect of positive physical adaptation to the vocational training of students in higher education [14]. Therefore, this study does not contradict these trends and offers an individually-differentiated approach to building physical education classes based on the availability and effectiveness of training in the educational process of the university.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the need for a gradual increase in physical activity is one of the key conditions for organizing physical education in the aspect of a health-improving orientation [16]. Violation of the principle of gradualness in the training process can not only not give the desired healing effect, but also lead to serious health problems [8].…”
Section: Introductionmentioning
confidence: 99%